Development of Vocabulary Training Module Using Games for Vocational English Teachers to Improve Teachers’ Competency - Pebrioni, Noni Melisa; Iriani, Ade; Dwikurnaningsih, Yari (Universitas Sebelas Maret, 2021)
The purpose of this study was to develop a vocabulary learning training module that contains games that can help vocational English teachers from SMK Saraswati, SMK Bhakti Nusantara, and SMKN 2 in Salatiga. Research and Development (R&D) approach was employed in this study. This study involved seven steps of the Borg and Gall model develop by Sugiyono model (2019), namely potential and problems, data collection, product design, design validation, design revision, product trial, and product revision. Ten vocational English teachers from SMK Saraswati, SMK Bhakti Nusantara, and SMKN 2 Salatiga participated in the study. Data collection techniques were done using document study, interview, and questionnaire. Data analysis was performed with qualitative-quantitative analysis. The result of the study were in the form of a vocabulary training module for English teachers with games. Based on the development of vocabulary training module, the resulting product is training modules that can be used and applied by teachers in carrying out teaching and learning activities in SMK Saraswati, SMK Bhakti Nusantara, and SMKN 2 in Salatiga and describe the application of games so that they can be used as a reference in teaching using games.